If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 9(x + 4) Reorder the terms: 6 + 3x = 9(x + 4) Reorder the terms: 6 + 3x = 9(4 + x) 6 + 3x = (4 * 9 + x * 9) 6 + 3x = (36 + 9x) Solving 6 + 3x = 36 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 6 + 3x + -9x = 36 + 9x + -9x Combine like terms: 3x + -9x = -6x 6 + -6x = 36 + 9x + -9x Combine like terms: 9x + -9x = 0 6 + -6x = 36 + 0 6 + -6x = 36 Add '-6' to each side of the equation. 6 + -6 + -6x = 36 + -6 Combine like terms: 6 + -6 = 0 0 + -6x = 36 + -6 -6x = 36 + -6 Combine like terms: 36 + -6 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) | | y+8=3(x+15) | | 70619.542=2*3.14*1303.21+2*3.14*36.1*h | | 2+4sinx=0 | | 422.67=c+.15c | | -(-4x+10-8y)= | | 8+3m-4=6m+9-2m | | 4x-5+x=7+5x-2 | | y+8=3(x+5) | | 3n-2(n+10)=n-20 | | 2w+6x-14y+8w+9x+6y= | | 81650.99=2*3.14*r^2+2*3.14*287.8*r | | 2m+1-4=-2m-3 | | 4(2x+1)=5x | | 7t-22=26+t | | (S-9)(s-1)=0 | | r+9r=-8 | | 18j-5=3(6j-2) | | 150=c+.18c | | 4x+(-8x)= |